The αvβ6 integrin receptor for Foot-and-mouth disease virus is expressed constitutively on the epithelial cells targeted in cattle - Monaghan, Paul; Gold, Sarah; Simpson, Jennifer; Zhang, Zhidong; Weinreb, Paul H.; Violette, Shelia M.; Alexandersen, Soren; Jackson, Terry (Journal of General Virology, 2005)
Field strains of Foot-and-mouth disease virus (FMDV) use a number of αv-integrins as receptors to initiate infection on cultured cells, and integrins are believed to be the receptors used to target epithelial cells in animals. In this study, immunofluorescence confocal microscopy and real-time RT-PCR were used to investigate expression of two of the integrin receptors of FMDV, αvβ6 and αvβ3, within various epithelia targeted by this virus in cattle. These studies show that αvβ6 is expressed constitutively on the surfaces of epithelial cells at sites where infectious lesions occur during a natural infection, but not at sites where lesions are not normally formed. Expression of αvβ6 protein at these sites showed a good correlation with the relative abundance of β6 mRNA. In contrast, αvβ3 protein was only detected at low levels on the vasculature and not on the epithelial cells of any of the tissues investigated. Together, these data suggest that in cattle, αvβ6, rather than αvβ3, serves as the major receptor that determines the tropism of FMDV for the epithelia normally targeted by this virus.